DEVELOPING A PLATFORM FOR TEACHER BLOGGING - Koshova, O. P.; Chernenko, O. O.; Komar, I. I. (Systems and Technologies, 2025)
The purpose of the article is to analyze the software architecture for a teacher’s blog and describe its main components that ensure effective content management and quick interaction with users. It covers approaches to developing an administrative web application and a public website, their interaction via API, as well as the use of modern technologies such as Next.js, MongoDB, and JWT to achieve system stability, scalability, and security.The software architecture consists of an administrative web application (Frontend and Backend) and a public website (Frontend). The administrative interface is built on the Next.js platform, which combines server-side rendering (SSR) and client-side rendering, ensuring high page loading speed. The frontend part allows teachers to manage blog content, including creating, editing, and deleting articles, books, and author information. The backend part is implemented for query processing, MongoDB database management, authentication, and access control via JWT. The public website uses static page generation (SSG) and SSR technologies, which ensure optimal performance and fast loading of content. Also considered are use cases, including administrator authorization, article, book and settings management. The Vercel platform was chosen for hosting, which provides automatic deployment via GitHub and CI/CD support.The results of the study confirm the effectiveness of the chosen architecture for ensuring fast and secure operation of the teacher’s blog. The use of Next.js, MongoDB, and JWT allows you to create a flexible and scalable system with the ability to expand functionality. The public website provides users with access to articles and books without authentication, and the administrative web application provides convenient content management. The selected technologies contribute to high productivity and ease of use of the system.